Transforming Nigerian food systems through their backbones: Lessons from a decade of staple crop biofortification programing - Birol, Ekin; Foley, Jennifer; Herrington, Caitlin; Misra, Rewa S.; Mudyahoto, Bho; Pfeiffer, Wolfgang; Diressie, Michael Tedla; Ilona, Paul (SAGE Publications, 2023)
This article presents the evolution of the biofortification program in Nigeria over the last decade and the role of interdisciplinary research in informing cost-effective, efficient, and inclusive development; implementation; and scaling of this program. Launched in 2011 to improve Nigeria’s food systems to deliver accessible and affordable nutrients through commonly consumed staples, the Nigeria biofortification program was implemented through an effective partnership between the CGIAR and public, private, and civil society sectors at federal, state, and local levels. By the end of 2021, several biofortified varieties of Nigeria’s 2 main staples, namely cassava and maize, were officially released for production by smallholders, with several biofortified varieties of other key staples (including pearl millet, rice, and sorghum) either under testing or in the release pipeline. In 2021, the program was estimated to benefit 13 million Nigerians consuming biofortified cassava and maize varieties. The evidence on the nutritional impact, consumer and farmer acceptance, and cost-effective scalability of biofortified crops documented by the program resulted in the integration of biofortified crops in several key national public policies and social protection programs; private seed and food company products/investments, as well as in humanitarian aid.